Superhydrophobic wood sponge with intelligent pH responsiveness for efficient and continuous oil-water separation - Bin Du; Bin Li; Kenan Yang; Yi Chao; Rubai Luo; Shisheng Zhou; Huailin Li (Materials Research Express, 2023)
In recent years, the leakage of crude oil and the discharge of oily wastewater in industrial production have seriously endangered the water environment and ecological safety. Adsorbent materials with excellent oil-water separation performance play an important role in water purification. In this work, we employed a simple yet effective strategy to prepare highly compressible wood sponges. And with the prepared wood sponge as the substrate, the prepared pH-responsive copolymer was coated on the surface of the wood sponge by spraying method, and the pH-responsive superhydrophobic wood sponge was successfully prepared. The experimental results show that the wood sponge has excellent pH-responsive properties and can complete the transition of surface wettability between superhydrophobicity and hydrophilicity according to the change of pH value. The wood sponge has good oil adsorption capacity (12.72 g g ^−1 ), and reusability. Continuous oil-water separation can be carried out under the vacuum pump, and the oil-water separation efficiency in one separation cycle is above 92%. It has great application potential in the treatment of oily wastewater.